Biological Functions and Cross-Kingdom Host Gene Regulation of Small RNAs in Lactobacillus plantarum-Derived Extracellular Vesicles - Yu, Siran; Zhao, Zhehao; Hao, Piliang; Qiu, Yan; Zhao, Meiyi; Zhou, Gang; Zhang, Chengqian; Kang, Jiuhong; Li, Ping (Frontiers in Microbiology, 2022)
Extracellular vesicle-mediated transfer of microRNAs is a novel mode of cell-to-cell genetic transmission. Extracellular vesicles produced by microbes have been shown to contain significant quantities of physiologically active molecules such as proteins, lipids, and RNAs, which could be transported to host cells and play a key role in both inter-kingdom signaling and physiological responses. In this study, we identified sRNAs by sequencing small RNAs (sRNAs) from Lactobacillus plantarum-derived extracellular vesicles (LDEVs) and detected the expression levels of vesicular sRNAs using quantitative reverse transcription polymerase chain reaction (RT-PCR), which demonstrated the presence of microRNA-sized RNAs (msRNAs) within these vesicles. We chose sRNA71, a highly expressed msRNA, for further investigation, predicted its potential target genes for human genome, and indicated that it could be translocated into mammalian cells. The biological functions of this sRNA were subsequently explored through cellular proteomics, western blot, and luciferase reporter assay. According to the findings, transfection with synthetic sRNA71 mimics substantially reduced Tp53 expression in HEK293T cells and suppressed the gene through binding to the 3' UTR of Tp53 mRNA. In conclusion, it is hypothesized that microbial-derived extracellular vesicles serve as carriers of functional molecules such as sRNAs, which play an essential role in regulating microbial-host communication.